PERBEDAAN PERKEMBANGAN ANTARA ANAK YANG STUNTING DAN NON-STUNTING (STUDI KASUS DI TK WILAYAH PUCANG GADING, JAWA TENGAH, INDONESIA) - Uswatun Khasanah; Suyatno Suyatno; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Children who are stunted can cause impaired motor system development because growth and development of 80% of the brain occurs during the first 1000 days of life. The purpose of this study was to determine differences in development in stunting and non-stunting children. This type of research is comparative with a cross sectional approach. Research locations in TK Pucang Gading Region, Central Java, Indonesia. The study population was 193 kindergartens. The research sample consisted of two groups namely stunting children (39 children) and non-stunting children (39 children) obtained by purposive sampling technique. The instruments used were the Pre Development Screening Questionnaire (KPSP) and microtoise. Data analysis using Chi Square statistical test. The results found that the incidence of stunting in Kindergarten in Pucang Gading Region was 37.3% and non-stunting was 62.7%. Developmental scores in stunting children are lower than in non-stunting children (8.77 versus 8.03 from a maximum score of 10) although both are still in the normal development category. Children whose developmental failures were lower occurred in non-stunting children compared to stunting children (35.9% versus 12.8%) therefore there were significant developmental differences between the two groups (p = 0.018). Chi square test results showed no relationship between parenting (p = 0.818), TKE (p = 0.431), TKP (p = 0.217), and TKKal (p = 0.700) with child development. Based on these results it is expected that parents of stunting children should further increase stimulation to support child development.